The drive to generate multiple forms of oncogenic cyclin D1 transcripts in mantle cell lymphoma - Chioniso Patience Masamha (BMC, 2017)
Abstract Alternative polyadenylation is a rapidly emerging form of gene regulation, which in its simplest form, enables the generation of mRNA transcripts that code for the same protein but have 3'UTRs of different lengths and regulatory content. For oncogenes, shorter 3'UTRs would be preferred as a mechanism to evade miRNA regulation. The shortening of the 3'UTR of cyclin D1 in mantle cell lymphoma offers provocative insights into this process. Patient samples have revealed that 3'UTR shortening may occur due to mutations, or translocations that result in the generation of a chimeric 3'UTR. The truncated cyclin D1 3'UTRs resulting from alternative polyadenylation, use a premature canonical polyadenylation signal close to the stop codon that was generated either as a result of mutations or provided by another gene in the chimeric 3'UTR. The sequence of the polyadenylation signal in mantle cell lymphoma appears to be critical for 3'end formation of the cyclin D1 transcript. Shortening the 3'UTR allows cyclin D1 to potentially evade regulation by over 80 miRNAs that are predicted to bind to its full length 3'UTR.